PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, REPUTASI KAP, DAN PERGANTIAN AUDITOR PADA KETIDAKTEPATWAKTUAN PELAPORAN KEUANGAN - Carbaja, Indah Christina; Yadnyana, I Ketut (E-Jurnal Akuntansi, 2015)
The information if not timely in submitting financial statements would be irrelevant and will lose the opportunity to influence decisions. The purpose of this study was to determine the effect of profitability, size of company, the firm's reputation, and the change of auditors on late publication. The research samples in study were 44 companies that are not timely financial reporting in Indonesia Stock Exchange year period from 2012-2013 were taken by purposive sampling method. Technical analysis of the data used is multiple linier analysis. The analysis showed that profitability, firm size, and the change of auditor’s effect on late publication, whereas the firm’s reputation does not have effect on the late financial report publication.
Keywords: profitability, size of company, the firm’s reputation, the change of auditors